2014
DOI: 10.1002/jez.1852
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium contaminated soil affects retinogenesis in lizard embryos

Abstract: Lizards are soil surface animals that represent an important link between invertebrates and higher predators. Being part of wild fauna, they can be affected by contamination from anthropic activities and in particular, pesticides and chemical substances of various nature that reach the soil surface directly or through fall out. Among these substances, heavy metals such as cadmium may exert particularly marked toxic effect on both adult and embryos. In lizards, recent studies show that cadmium may cause develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…In situ hybridization was carried out as described elsewhere (Agnese et al, ; Agnese, Valiante, Rosati, Andreuccetti, & Prisco, ; Prisco et al, ; Simoniello et al, ). Dig‐labeled ER1 and ER2 complementary DNA probes were generated by PCR using the Dig‐DNA labeling mix (Roche Diagnostics, Indianapolis, IN).…”
Section: Methodsmentioning
confidence: 99%
“…In situ hybridization was carried out as described elsewhere (Agnese et al, ; Agnese, Valiante, Rosati, Andreuccetti, & Prisco, ; Prisco et al, ; Simoniello et al, ). Dig‐labeled ER1 and ER2 complementary DNA probes were generated by PCR using the Dig‐DNA labeling mix (Roche Diagnostics, Indianapolis, IN).…”
Section: Methodsmentioning
confidence: 99%
“…Developing embryos can also be exposed to metals through the egg shell (Marco et al 2004). Consequently, absorption of Cd can cause malformation of eye development in the Italian wall lizard (Podarcis sicula) (Simoniello et al 2014) and the running speed of hatchling Iberian rock lizard (Iberolacerta monticola) was negatively correlated with embryonic As absorption (Marco et al 2004). Metal body burdens or exposure levels that cause physiological or behavioural alterations in the aforementioned studies are well above what we observed in the livers of our adult tiger snakes from the Swan Coastal Plain; however, chronically contaminated reptiles are susceptible to a variety of pernicious developmental and behavioural disorders.…”
Section: Potential Impacts To Snakesmentioning
confidence: 99%
“…This evolutionary conserved epigenetic mark [9] occurs via covalent addition of a methyl (CH 3 ) group to the 5 -carbon position of cytosine pyrimidine ring primarily found in cytosine-guanine (CpG) dinucleotides [10]. Global and gene-specific changes in 5mC content associated with Cd exposure have been described in most vertebrate classes [11][12][13][14][15]. However, limited information exists for terrestrial invertebrates routinely used as sentinel organisms, such as annelids [16] or land snails [7].…”
Section: Introductionmentioning
confidence: 99%